Mengungkap Potensi Limbah: Analisis Nutrisi Jeroan Teripang (Holothuria sp.) sebagai Pakan Fungsional - Muhsin, Muhammad Fatratullah; Rozaimi, Rusydi; Alimin, Ade Wahyul Fajri; Pangloli, Nur Yanti; Fujaya, Yushinta; Hidayani, Andi Aliah; Waiho, Khor; Achmad, Marlina (Torani Journal of Fisheries and Marine Science, 2025)
Sea cucumber (Holothuria sp.) viscera, commonly considered as waste in the sea cucumber processing industry, has been proven to possess significant nutritional value be utilized as a potential functional feed ingredient. This study aimed to evaluate the nutritional content of sea cucumber viscera and assess its potential use as a supplementary feed ingredient in aquaculture. Proximate analysis results indicated that sea cucumber viscera contain high crude protein (39.69 ± 0.38 %) and crude fat (26.62 ± 0.41 %). A complete profile of essential amino acids was identified, with arginine (6,621.7 mg/kg) being the highest. Furthermore, sea cucumber viscera were dominated by polyunsaturated fatty acids (PUFA) at 52.89 %, including EPA (6.73 %) and DHA (7.46 %). Significant vitamin and mineral contents were also found, such as vitamin A (4.16 µg/g), vitamin C (84.67 µg/g), calcium (1,701.72 mg/L), and magnesium (542.38 mg/L). These findings highlight the potential of sea cucumber viscera as a crucial source of energy, protein, essential fatty acids, vitamins, and minerals for the growth and health of aquaculture organisms. Utilizing sea cucumber viscera as a feed ingredient not only provides a high-nutritional alternative feed but also supports circular economy and zero-waste principles in marine waste management.